How to exploit different endocytosis pathways to allow selective delivery of anticancer drugs to cancer cells over healthy cells. Issue 46 (18th November 2021) - Cong, Vu Thanh; Tilley, Richard D.; Sharbeen, George; Phillips, Phoebe A.; Gaus, Katharina; Gooding, J. Justin
Abstract : It was recently shown that it is possible to exploit the nanoparticle shape to selectively target endocytosis pathways found in cancer and not healthy cells. Abstract : It was recently shown that it is possible to exploit the nanoparticle shape to selectively target endocytosis pathways found in cancer and not healthy cells. It is important to understand and compare the endocytosis pathways of nanoparticles in both cancer and healthy cells to restrict the healthy cells from taking up anticancer drugs to help reduce the side effects for patients. Here, the clathrin-mediated endocytosis inhibitor, hydroxychloroquine, and the anticancer drug, doxorubicin, are loaded into the same mesoporous silica nanorods. The use of nanorods was found to restrict the uptake by healthy cells but allowed cancer cells to take up the nanorods via the macropinocytosis pathway. Furthermore, it is shown that the nanorods can selectively deliver doxorubicin to the nucleus of breast cancer cells and to the cytoplasm of pancreatic cancer cells. The dual-drug-loaded nanorods were able to selectively kill the breast cancer cells in the presence of healthy breast cells. This study opens exciting possibilities of targeting cancer cells based on the material shape rather than targeting antibodies.